2015
DOI: 10.1007/s11011-015-9689-6
|View full text |Cite
|
Sign up to set email alerts
|

Possible cause for altered spatial cognition of prepubescent rats exposed to chronic radiofrequency electromagnetic radiation

Abstract: The effects of chronic and repeated radiofrequency electromagnetic radiation (RFEMR) exposure on spatial cognition and hippocampal architecture were investigated in prepubescent rats. Four weeks old male Wistar rats were exposed to RF-EMR (900 MHz; SAR-1.15 W/kg with peak power density of 146.60 μW/cm(2)) for 1 h/day, for 28 days. Followed by this, spatial cognition was evaluated by Morris water maze test. To evaluate the hippocampal morphology; H&E staining, cresyl violet staining, and Golgi-Cox staining were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 54 publications
1
11
1
Order By: Relevance
“…found that Wistar rats exposed to RF-EMR (900 MHz; peak power density of 146.60 μW/cm 2 ) for 1 h/day for 28 consecutive days had significantly reduced dendritic branch points at the 40–60 μm concentric zone, and a progressive decrease in learning abilities measured using the Morris water maze test. They concluded that structural changes in the hippocampus in RF-EMR-exposed rats could be one possible reason for their altered cognitive abilities25. Although our results conversely indicated a positive effect of RF-EMR exposure in terms of enhanced novel object recognition and a parallel increase in spine density in hippocampal neurons, the relationship between hippocampal spine density and recognition memory was still retained.…”
Section: Discussioncontrasting
confidence: 56%
“…found that Wistar rats exposed to RF-EMR (900 MHz; peak power density of 146.60 μW/cm 2 ) for 1 h/day for 28 consecutive days had significantly reduced dendritic branch points at the 40–60 μm concentric zone, and a progressive decrease in learning abilities measured using the Morris water maze test. They concluded that structural changes in the hippocampus in RF-EMR-exposed rats could be one possible reason for their altered cognitive abilities25. Although our results conversely indicated a positive effect of RF-EMR exposure in terms of enhanced novel object recognition and a parallel increase in spine density in hippocampal neurons, the relationship between hippocampal spine density and recognition memory was still retained.…”
Section: Discussioncontrasting
confidence: 56%
“…Adding to the debate is the lack of a characterized mechanism by which RF-EMR could affect biological systems. There is broadly, two opposing bodies of evidence, some that support the potential of RF-EMR to elicit a suite of detrimental effects in a variety of cell and tissues types including altered brain nerve branching ( 9 ), oxidative stress ( 10 – 14 ), genotoxic assault highlighted by micronuclei formation ( 15 , 16 ), and DNA fragmentation ( 13 , 17 , 18 ), while some find no elevation of oxidative stress ( 19 21 ) or DNA damage ( 22 24 ). The absence of a widely accepted mechanism of action that may account for the effects observed, complicates our ability to understand how RF-EMR interacts with specific cell types and to resolve the disparity in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the fact that mechanisms such as LTP, calcium signaling, cell cycle regulation, and death were affected may be associated with the increased Ca 2+ influx, apoptosis, synaptic changes, pyramidal cell loss, and reactive astrocytosis, which all have been reported to occur following MP radiation exposure (Bas, Odaci, Mollaoglu, Ucok, & Kaplan, ; Bas, Odaci, Kaplan, et al., ; Li et al., ; Maskey et al., ; Moghimi, Baharara, & Musavi, ; Narayanan et al., ; Odaci, Bas, & Kaplan, ; Sahin et al., ) and hence lead to learning and memory deficits, as previously reported by our group (Fragopoulou et al., ) and other groups (Li et al., ; Moghimi et al., ; Narayanan et al., ; Saikhedkar et al., ; Wang et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Hippocampus is integral to memory function and is a brain region greatly affected by mobile phone (MP) radiation. Several studies have documented mobile phone‐related learning and memory impairment in mice and rats (Fragopoulou et al., ; Hao et al., ; Li, Shi, Lu, Xu, & Liu, ; Narayanan, Kumar, Karun, Nayak, & Bhat, ; Narayanan, Kumar, Potu, Nayak, & Mailankot, ; Ntzouni, Skouroliakou, Kostomitsopoulos, & Margaritis, ; Ntzouni, Stamatakis, Stylianopoulou, & Margaritis, ), while others failed to provide any evidence connecting RF‐EMR with memory deficits (Dubreuil, Jay, & Edeline, ).…”
Section: Introductionmentioning
confidence: 99%